Long-term survival with gemcitabine and docetaxel for renal leiomyosarcoma a case report - Nagumo, Yoshiyuki (Hinyokika kiyo. Acta urologica Japonica, 2013)
A 64-year-old woman who complained of abdominal pain underwent right radical nephrectomy under the clinical diagnosis of renal cell carcinoma in January, 2006. The pathological diagnosis was leiomyosarcoma originating from the kidney. Follow-up computed tomography revealed 2 small nodules in the left lung 15 months after nephrectomy. A lung nodule resected with video-assisted thoracic surgery (VATS) was identified as metastatic leiomyosarcoma. Since the pulmonary metastases progressed after VATS, systemic chemotherapy with gemcitabine and docetaxel (GD therapy) was started. The lung metastases responded well, and a durable partial response was achieved for 29 months. Subsequently, the patient developed new pulmonary metastases and pancreatic metastasis. Despite this disease progression, we elected to continue GD therapy, since the patient's performance status and quality of life were favorable during the treatment. So far, the GD therapy has been continued for another 23 months, for a total of 41 treatment cycles, with few adverse events. Although multiple metastases have slowly progressed, the patient has maintained good performance status in the outpatient clinic. In the present case, GD therapy seems to have been beneficial for survival, as metastatic renal leiomyosarcoma is considered to have an extremely poor prognosis